Analytical stress-strain model of hybrid FRP-concrete-steel double skin tubular columns under axial compression. (1st July 2023) - Bhat, Pronnoy; Jamatia, Rimen
Highlights: Analytical model for confining pressure exerted by outer FRP and inner steel tube on sandwiched concrete in hybrid FRP-Concrete-Steel Double Skin Tubular Columns (DSTC) under axial compression is proposed. Analysis-oriented model is proposed for predicting the axial stress–strain behavior of DSTC and validated with available experimental data from the literature. Abstract: An analytical model is proposed for confinement pressure exerted by outer fibre-reinforced polymer (FRP) and inner steel tube on sandwiched concrete in hybrid FRP-concrete-steel double skin tubular columns (DSTC) under axial compression assuming displacement compatibility between both FRP-concrete and steel–concrete interfaces. Next, using the proposed analytical model, an analysis-oriented model is presented to predict the uniaxial behavior of hybrid FRP-concrete-steel DSTC. Comparison with available test results from the literature shows that the proposed model provides reasonably good predictions compared to other existing models.